2018
DOI: 10.1007/s00262-018-2169-1
|View full text |Cite
|
Sign up to set email alerts
|

VISTA expression on tumor-infiltrating inflammatory cells in primary cutaneous melanoma correlates with poor disease-specific survival

Abstract: Adaptive immune responses contribute to the pathogenesis of melanoma by facilitating immune evasion. V-domain Ig suppressor of T-cell activation (VISTA) is a potent negative regulator of T-cell function and is expressed at high levels on monocytes, granulocytes, and macrophages, and at lower densities on T-cell populations within the tumor microenvironment. In this study, 85 primary melanoma specimens were selected from pathology tissue archives and immunohistochemically stained for CD3, PD-1, PD-L1, and VISTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 32 publications
1
74
1
Order By: Relevance
“…We also found that normal human organs other than lymphoid tissues and placental trophoblastic cells did not express VISTA at the protein level [13]. Although VISTA protein has been detected in gastric cancer, oral squamous cell carcinoma, NSCLC, colorectal carcinoma, hepatocellular carcinoma, endometrial cancer, ovarian cancer, melanoma, and gestational trophoblastic neoplasia, its expression and relationship with patient survival vary according to the type of cancer [13][14][15][16][17][18][19][20][21]. While VISTA was mainly expressed by tumor-infiltrating lymphocytes, it was only present in 8.8% of gastric cancer cells and in 19.4-22.8% of NSCLC lesions [15,16].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We also found that normal human organs other than lymphoid tissues and placental trophoblastic cells did not express VISTA at the protein level [13]. Although VISTA protein has been detected in gastric cancer, oral squamous cell carcinoma, NSCLC, colorectal carcinoma, hepatocellular carcinoma, endometrial cancer, ovarian cancer, melanoma, and gestational trophoblastic neoplasia, its expression and relationship with patient survival vary according to the type of cancer [13][14][15][16][17][18][19][20][21]. While VISTA was mainly expressed by tumor-infiltrating lymphocytes, it was only present in 8.8% of gastric cancer cells and in 19.4-22.8% of NSCLC lesions [15,16].…”
Section: Discussionmentioning
confidence: 75%
“…These studies suggest that VISTA may modulate a novel immune evasion mechanism and is thus a potential target for cancer immunotherapy. VISTA expression in human cancers has been reported in non-small cell lung cancer (NSCLC), hepatocellular carcinoma, colorectal carcinoma, oral squamous cell carcinoma, gastric carcinoma, acute myeloid leukemia, and gestational trophoblastic neoplasia [13][14][15][16][17][18][19][20][21]. Mulati et al also found that VISTA was highly expressed in human ovarian and endometrial cancers [20].…”
Section: Introductionmentioning
confidence: 98%
“…The ability of TAMs to limit the efficacy of ICB therapy has been demonstrated [43,44]. TAMs express ligand molecules for checkpoint receptors, such as PD-L1/2, CD80, CD86 and VISTA (V-domain immunoglobulin suppressor of T cell activation), and possibly others; the presence of checkpoint inhibitors different from those targeted by the currently available antibodies cancels the benefit of the therapy and maintains a state of strong immunosuppression [40,[45][46][47]. The expression of PD-L1 by TAMs results in the sequestration of anti-PD-L1 mAbs [45].…”
Section: Interaction Of Tams With Immune-checkpoint Blockade Therapymentioning
confidence: 99%
“…In both studies, growth differences were not observed in fully immune‐incompetent mice, indicating that VISTA expressed on tumor cells is able to impair anti‐tumor immunity. Interestingly, although initial studies showed minimal expression of VISTA on human tumor cells and suggested a predominant myeloid expression in the tumor , a number of recent studies have established that while some tumor types such as melanoma are associated with immune‐restricted VISTA expression , tumor cells can show significant expression on CD45‐negative tumor cells. This has been demonstrated in gastric cancer , ovarian cancer , colorectal cancer and primary oral squamous cell mesothelioma .…”
Section: Vista Expression In On Non‐hematopoietic Cells In Cancermentioning
confidence: 99%
“…In colon cancer, analysis of the The Cancer Genome Atlas (TGCA) database showed association of high VISTA expression with poor OS . While expression of VISTA (or PD‐1 and CTLA‐4) in cutaneous melanoma by analysis of the TGCA database showed a positive association with survival, immunohistochemistry staining (IHC) demonstrated that high VISTA expression on immune cells was associated with poor survival . In ovarian cancer, while VISTA expression was not predictive for OS, VISTA expression increased with progression, and was generally increased in advanced disease .…”
Section: Vista Expression In Tumor‐infiltrating Immune Cellsmentioning
confidence: 99%